Ar-Rohmah English week: Expanding English for Young Learners program in an Indonesian Islamic primary school - Rina Wahyu Setyaningrum; Rafika Rabba Farah; Puji Sumarsono; Lailatul Rifah (Universitas Muhammadiyah Malang, 2023)
English is an elective subject at Indonesian primary schools and every school is allowed to offer English for providing young learners (YLs) opportunity to practice English for communication in global society. Moreover, English is introduced earlier in primary education as an extra-curricular activity as well as a locally-tailored school subject. This community service program aims at facilitating the sixth graders with extended activities to support the English for Young Learners (EYL) program that they have attended for six years and preparing them with initial experience before enrolling in English a compulsory subject class in lower secondary education. Ar-Rohmah English Week was conducted for 60 minutes within four working days with activities to enhance the YLs’ English listening, speaking, reading, and writing. Four activities were selected based on the learners’ needs within meaningful activities such as Virtual Tour to the USA, Reading Theater, Students’ Activities Journaling which infuses Islamic content, and Act Out and Presentation. All of those activities were also designed by addressing the United Nations Sustainable Development Goals 2030 (UN SDGs 2030) number 4 on quality education. With their English proficiency, all students are expected to be able to compete in mastering various knowledge in facing global challenges in the future.